Utility of CAD/CAM technology in the dental prostheses manufacture - Washington Paúl Culqui Molina; Jonathan Wagner Robles Caisaguano; Marcelo Alexander Ramos Núñez (Medisur)
CAD/CAM technology is an innovative way related to the implementation of digital techniques to improve prosthetic restorations in a patient, including those intended for dental aesthetics. The objective of this study is to describe the usefulness of CAD/CAM technology in the dental prostheses manufacture. A review of the medical literature available in the PubMed/Medline, Scopus and SciELO databases was carried out, using advanced search formulas; Articles in Spanish and English were selected. Currently, with this technology it has been possible to combine aesthetics, resistance and precision in direct restoration, in addition to guaranteeing greater duration and years of functionality for each of the prostheses, crowns and implants. The quality of life and satisfaction reported by patients wearing parts produced with this technology is higher than those reported by those treated with traditionally manufactured parts. The use of artificial intelligence and biomaterials techniques will represent a qualitative and quantitative change in the use of CAD/CAM systems.